PENERAPAN KONSEP TEORI MODEL KEPERAWATAN MADELEINE M LEININGER MODEL KONSEPTUAL KULTUR KEPERAWATAN PADA ASUHAN KEPRAWATAN ULKUS CRURIS DEXTRA DI RUANGAN RAWAT INAP - Suharjo Suharjo; Irna Nursanti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
This study discusses the application of nursing care to Mrs. S with dextra cruris ulcers, referring to the nursing model and theory of Madeleine M. Leininger's concept. The case study method was used with a nursing approach based on Leininger's theory. Data were collected through interviews, observations, physical examinations, and documentation studies using an assessment format according to the theory. The results of the assessment identified factors such as technology, social, cultural values, policies, economics, and education that influence nursing care. Two nursing problems were found, namely Ineffective Health Maintenance and ineffective breathing patterns. Interventions were based on the Standardized Individualized Nursing Steps and Standardized Individualized Nursing Interactions. After three days of nursing care, both problems were partially resolved. The conclusion of the study emphasizes the importance of nurses in providing quality nursing care with the Madeleine M. Leininger approach. It is hoped that this will improve overall nursing services.